2022
DOI: 10.1007/s40744-022-00434-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Secukinumab on Traditional Cardiovascular Risk Factors and Inflammatory Biomarkers: Post Hoc Analyses of Pooled Data Across Three Indications

Abstract: Background Psoriasis, psoriatic arthritis (PsA), and axial spondyloarthritis (axSpA) are chronic immune-mediated inflammatory diseases (IMIDs) associated with cardiovascular (CV) disease. High-sensitivity C-reactive protein (hsCRP) and, more recently, the neutrophil–lymphocyte ratio (NLR) are important inflammatory biomarkers predictive of CV disease and CV disease-associated mortality. Here, we report the effect of interleukin (IL)-17A inhibition with secukinumab on CV risk parameters in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Clinical trial data for several anti-IL-17 and anti-IL-23p19 antibodies suggested no cardiovascular safety signals [46][47][48][49][50]. In a post hoc analysis of pooled phase 3 and 4 data in patients with psoriasis, secukinumab treatment reduced the inflammatory biomarkers' high-sensitivity C-reactive protein and neutrophil-lymphocyte ratio with no effect on traditional cardiovascular risk parameters compared with placebo [51]. Postmarketing data for the IL-17A antibody secukinumab also contained no cardiovascular safety signals; the exposure-adjusted incidence rate of MACE per 100 patient-years over the entire treatment period remained low for each indication (psoriasis, psoriatic arthritis, and ankylosing spondylitis) [52].…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…Clinical trial data for several anti-IL-17 and anti-IL-23p19 antibodies suggested no cardiovascular safety signals [46][47][48][49][50]. In a post hoc analysis of pooled phase 3 and 4 data in patients with psoriasis, secukinumab treatment reduced the inflammatory biomarkers' high-sensitivity C-reactive protein and neutrophil-lymphocyte ratio with no effect on traditional cardiovascular risk parameters compared with placebo [51]. Postmarketing data for the IL-17A antibody secukinumab also contained no cardiovascular safety signals; the exposure-adjusted incidence rate of MACE per 100 patient-years over the entire treatment period remained low for each indication (psoriasis, psoriatic arthritis, and ankylosing spondylitis) [52].…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…The role of adaptive immunity (Th1 and Th17 cells) and IL-17 in the pathogenesis of hypertension has been confirmed by its actions on the proximal and distal tubules, in the thick ascending limb, and the epithelial sodium channel in the collecting duct 39 . Notably, the sole use of SCK did not show benefits in blood pressure in patients with psoriasis, psoriatic arthritis, and axial spondyloarthritis 40 . Further investigation is needed to determine whether the decrease in hypotensive drugs in our patients results from the effect of IL-17A blockade on the arteries, renal environment, or both.…”
Section: Discussionmentioning
confidence: 92%
“…TNF inhibitors were associated with a reduced risk of CVD according to the retrospective follow-up analysis of 5046 SpA patients [ 5 ]. Secukinumab and ixekizumab were the selective IL-17A inhibitors that improved the degree of systemic inflammation without negatively impacting traditional CV risk factors [ 5 , 46 , 47 ]. There were questionable relationships between the targeted synthetic DMARDs and MACE risk in SpA patients [ 45 , 48 50 ].…”
Section: Discussionmentioning
confidence: 99%